Distribution patterns and ecological risk of endocrine-disrupting chemicals at Qingduizi Bay (China): A preliminary survey in a developing maricultured bay. (September 2019) - Wang, Lili; Yang, Xiaolong; Zhang, Anguo; Bidegain, Gorka; Li, Ruijing; Na, Guangshui; Yuan, Xiutang
Abstract: The occurrence and estrogenic activities of seven phenolic endocrine-disrupting chemical (EDC) compounds (nonylphenol (NP), octylphenol (4-OP), 2, 4-dichlorophenol (2, 4-DCP), 4-tertbutylphenol (4- t -BP), 4-tert-octylphenol (4- t -OP), tetrabromobisphenol A (TBBPA), and bisphenol A (BPA)) in the sediments of Qingduizi Bay (NorthernYellow Sea, China) in superficial sediments were investigated to evaluate their potential ecological impacts on the health of aquaculture organisms. All compounds, except 4-OP and 4- t -BP, were recorded in most sampling sites (1.06–28.07 ng g −1 dw in maricultural ponds (MPs), 1.98–8.22 ng g −1 dw in outer bay (OB)). BPA and 4- t -OP were the predominant EDC compounds in MPs and OB, respectively. Correlation between BPA and 4- t -OP indicated these compounds may share a similar source or pathway. Analyzed estrogenic activity revealed a low risk of total EDCs. The ranking of risk quotient showed 4- t -OP posed a median risk and TBBPA posed a high risk to the aquatic ecosystem. Highlights: Comparative study of levels and potential risk of EDCs in mariculture ponds and outer bay. EDCs present low levels compared to other coastal areas. Poor correlation between EDC compounds and geochemical factors. TBBPA and 4- t -OP showed high and median risk for aquatic life, respectively.